2009
DOI: 10.1007/s11665-009-9407-9
|View full text |Cite
|
Sign up to set email alerts
|

SmartFlex® NiTi Wires for Shape Memory Actuators

Abstract: Shape memory alloys (SMAs) are active metallic materials classified nowadays as ''smart'' or ''intelligent'' materials. One of their main areas of interest is that of actuators. The use of SMAs in actuators offers the opportunity to develop robust, simple, and lightweight elements that can represent an alternative to electro-magnetic actuators commonly used in several fields of industrial applications, such as automotive, appliances, etc. SAES Getters S.p.A. thanks to its vertically integrated process and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 2 publications
2
63
0
2
Order By: Relevance
“…There are a limited number of studies in the literature concerning the thermo-mechanical fatigue of shape memory alloys (Bertacchini et al, 2009;Bigeon and Morin, 1996;Lagoudas et al, 2009Lagoudas et al, , 2000 and even fewer studies addressing the thermo-mechanical fatigue behavior of Nitinol (Fumagalli et al, 2009;Mertmann and Vergani, 2008;Scirè Mammano and Dragoni, 2014). Although many researchers have referred to the failure under coupled thermal and mechanical loads as functional fatigue, this type of failure is, in fact, thermo-mechanical fatigue.…”
Section: Thermo-mechanical Fatiguementioning
confidence: 99%
“…There are a limited number of studies in the literature concerning the thermo-mechanical fatigue of shape memory alloys (Bertacchini et al, 2009;Bigeon and Morin, 1996;Lagoudas et al, 2009Lagoudas et al, , 2000 and even fewer studies addressing the thermo-mechanical fatigue behavior of Nitinol (Fumagalli et al, 2009;Mertmann and Vergani, 2008;Scirè Mammano and Dragoni, 2014). Although many researchers have referred to the failure under coupled thermal and mechanical loads as functional fatigue, this type of failure is, in fact, thermo-mechanical fatigue.…”
Section: Thermo-mechanical Fatiguementioning
confidence: 99%
“…One powerful mechanism is the shape memory effect of alloy materials since this mechanism has an ability to recover large transformation when it is heated and cooled. Among various shape memory alloy (SMA) materials, nickel-titanium, or nitinol (NiTi), is especially attractive due to its low-operating temperature, large deflection, and actuating force (Ref [1][2][3][4][5][6][7][8][9][10]. For the integration into microsystems, shape memory materials in thin-film form are extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Fumagalli et al have shown that for the most often used NiTi SMA total actuation cycles well above 10 6 are feasible if the strains and stresses are kept below 1-3% resp. 100-300 MPa but will drop below 3 × 10 5 if strains and stresses are above those margins [22]. The results are schematically depicted in Figure 24.4.…”
Section: Sma Overview and Important Propertiesmentioning
confidence: 95%
“…Fatigue lifetime for Smartflex 76 SMA wire under different stress-strain conditions [22]. as described before, the SMA element only produces an actuation stress or force ( Figure 24.5(b)).…”
Section: Characterization and Modeling Of Smamentioning
confidence: 98%